(untitled) (Third Sector Social Economic Review, 2023)
In this study, universities with ""Aviation Management"" and ""Civil Air Transportation Management"" departments affiliated with the Council of Higher Education were examined multidimensionally using the content analysis method. The data to be analyzed was obtained through the Higher Education Program Atlas (YÖK Atlas). The aim of this study is to reveal the current status of the ""Aviation Management"" department and the ""Civil Air Transport Management"" program and to offer suggestions for the future, taking into account the importance of these fields at the national level. As a result of this study, universities with ’’Aviation Management’’ and ’’Civil Air Transportation Management’’ departments affiliated with the Council of Higher Education; the dimensions were examined as university type, city and region, department program type (undergraduate/associate degree), department academic staff structure, number of quotas, number of students placed in the program, number of registered students, and language of instruction. The findings obtained as a result of the review are presented comprehensively. In the light of the findings, ""Aviation Management"" and ""Civil Air Transportation Management"" programs are included in state and foundation universities in Turkey; The quotas given mean that the number of students who are placed in the free programs of state universities and the scholarship programs of foundation universities is higher than the number of students who are placed in the paid evening education programs of state universities and the paid, 50% scholarship and 25% scholarship programs of foundation universities; There are more doctor lecturers and research assistants in the academic staff; It was determined that 5,012 students were enrolled in the ""Aviation Management"" department and 6,415 students were enrolled in the ""Civil Air Transportation Management"" program. As a result of the findings, it is seen that the demand for these two departments in Turkey is high, more students receive education in state universities, the number of academic staff is sufficient in line with the development process of the departments, and the quotas defined for the ""Aviation Management"" department and the ""Civil Air Transport Management"" program are full. has been determined to be provided. As a result of this study, it is seen that the demand for departments due to the development of the aviation sector is in parallel with the developments in the sector and as a result, training is offered to businesses in the sector to provide qualified workforce.